2022
DOI: 10.1002/advs.202104594
|View full text |Cite
|
Sign up to set email alerts
|

Remediating Desmoplasia with EGFR‐Targeted Photoactivable Multi‐Inhibitor Liposomes Doubles Overall Survival in Pancreatic Cancer

Abstract: Desmoplasia is characteristic of pancreatic ductal adenocarcinoma (PDAC), which exhibits 5‐year survival rates of 3%. Desmoplasia presents physical and biochemical barriers that contribute to treatment resistance, yet depleting the stroma alone is unsuccessful and even detrimental to patient outcomes. This study is the first demonstration of targeted photoactivable multi‐inhibitor liposomes (TPMILs) that induce both photodynamic and chemotherapeutic tumor insult, while simultaneously remediating desmoplasia in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 68 publications
(152 reference statements)
0
37
0
Order By: Relevance
“…Another randomized clinical trial (NCT02030860) evaluated neoadjuvant paricalcitol with GEM/Nab-PTX in resectable PDAC patients. In addition to VDR signaling activation, photodynamic therapy (PDT) has also been reported to decrease ECM density, increase collagen nonalignment, and improve drug delivery ( Obaid et al, 2019 ; Obaid et al, 2022 ). Patients who are refractory to GEM require high-dose administration, but intolerable toxicities are major concerns.…”
Section: Pdac Tme and Chemoresistancementioning
confidence: 99%
“…Another randomized clinical trial (NCT02030860) evaluated neoadjuvant paricalcitol with GEM/Nab-PTX in resectable PDAC patients. In addition to VDR signaling activation, photodynamic therapy (PDT) has also been reported to decrease ECM density, increase collagen nonalignment, and improve drug delivery ( Obaid et al, 2019 ; Obaid et al, 2022 ). Patients who are refractory to GEM require high-dose administration, but intolerable toxicities are major concerns.…”
Section: Pdac Tme and Chemoresistancementioning
confidence: 99%
“…However, very recently, Obaid and collaborators [ 110 ] reported on the synthesis of a single nanosystem (e.g., a cetuximab antibody-targeted liposome (EGFR-TPMIL)) for the co-delivery of IRI and a lipidated version of BPD for the concomitant pancreatic ductal adenocarcinoma (PDAC) treatment and associated desmoplasia remediation. Indeed, using MIA PaCa-2 cells as an in vitro PDAC model, the authors demonstrated that cetuximab-conjugated TPMIL increased up to 34-folds of the specificity of liposome binding to EGFR-overexpressing cells with respect to the untargeted counterpart (PMIL), thus confirming the tumor specificity of the targeted nanoconstruct as well as the exceptional photo-toxic effect determined after a 690 nm light cells activation (IC 50 measured for TPMIL decreased by 21-folds with respect to that for untargeted PMIL).…”
Section: Drug Delivery Systems For Pss and Chemotherapeutics: An Over...mentioning
confidence: 99%
“…Photodynamic therapy (PDT) has been demonstrated as a minimally invasive method to treat various types of cancer, including breast cancer, melanoma, and lung cancer ( Tang et al, 2021 ; Ding et al, 2022 ; Jia et al, 2022 ; Obaid et al, 2022 ; Pan et al, 2022 ; Zhang et al, 2022 ). The photosensitizers can be activated under a light source to generate reactive oxygen species (ROS) to kill cancer cells.…”
Section: Photothermal Therapy On Bc Metastasismentioning
confidence: 99%